Adequacy And Rate Of Atypical Cytology On Fine Needle Aspiration Technique Using Suction (FNA-S) – A Quality Assurance Study At CMCVAMC. (28th October 2020) - Dalal, S; Jhala, D
Abstract: Introduction/Objective: Thyroid cancer is one of the most common prevailing conditions. Both genetic and environmental risk factors play a role in causation of thyroid cancers, with agent orange being the most documented risk factor in Veteran patient population. Based on the ultrasonographic appearance, thyroid nodules can be further investigated by minimally invasive fine needle cytology. This can be done by either of two available techniques, Fine needle aspiration with suction (FNA-S) and Fine needle capillary cytology without using suction (FNC), depending upon the preference of practicing endocrinologist. We aim to compare both cytology techniques for comparing the diagnostic yield and rate of atypia of undetermined significance (AUS) or Follicular lesion of undetermined significance (FLUS), requiring repeat FNA in approximately three months. Methods: Retrospective study was conducted by searching the cases performed by an endocrinologist at Corporal Michael J Crescenz VA Medical Center between the period of January 1, 2015 and July 2, 2015. 30 nodules from 11 patients were tested by Fine needle capillary cytology technique (FNC). Yield for the diagnosis with rates of atypical (AUS) cytology were compared. On second set of the 29 patients with 38 nodules, both techniques - FNA-S versus FNC were carried out. Adequacy and rate of AUS/FLUS were calculated. Results: Out of 30 total nodules performed by fine needle aspiration (FNA-S), all cases yielded diagnostic material. Of them, 14 (46.6%) were diagnosed as AUS and 16 (53.33%) were benign. On the follow-up/re-aspiration by FNC technique, all these 14 nodules were diagnosed benign. On second set of patients on whom both techniques (FNA-S and FNC) were used alternatively, 13 of 38 nodules (34.21%) were diagnosed as AUS/FLUS, 23 (60.52%) were benign/nodular goiter and 2 were non-diagnostic/inadequate (5.2%). Conclusion: FNA-S (with suction) yields adequate diagnostic material, however, also has greater number of atypical cytology results requiring repeat patient visit which may increase morbidity with a burden on total health care cost. FNC (without suction) has low rates of AUS/FLUS, is diagnostically superior with excellent smear quality, less blood clots, time savings, and less inconvenience of patients/physician. FNC (without suction) is a modality of choice for an effective screening of thyroid nodules in veterans.